2022
DOI: 10.1590/2317-1782/20212021046
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and self-perceived health of adolescents in Middle School

Abstract: Purpose Quality of life and self-perception of health are useful indicators for children and adolescents, as they are associated with objective and subjective states of health, including physical, cognitive, social, emotional, and environmental aspects. This study aims to characterize the adolescents at a Brazilian private financing school and to analyze the association between quality of life, health self-perception, and the sociodemographic profile. Methods This is a cross-sectional, observational study con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Also, our results showed that students' better quality of life is associated with higher selfperceived health. This is consistent with a recent study by Fernandes et al 2022, which found that having a positive health self-perception improved the likelihood of having a good quality of life [62].…”
Section: Discussionsupporting
confidence: 93%
“…Also, our results showed that students' better quality of life is associated with higher selfperceived health. This is consistent with a recent study by Fernandes et al 2022, which found that having a positive health self-perception improved the likelihood of having a good quality of life [62].…”
Section: Discussionsupporting
confidence: 93%
“…Our analyzes indicate that quality of life is most often seen from a perspective that resembles health, including physical, cognitive, social, emotional and environmental aspects (3) . These are one of the indicators that aim to promote understanding of different aspects of health conditions experienced by healthy people from all cultures, including children and adolescents (2,3) .…”
Section: Discussionmentioning
confidence: 98%
“…Our analyzes indicate that quality of life is most often seen from a perspective that resembles health, including physical, cognitive, social, emotional and environmental aspects (3) . These are one of the indicators that aim to promote understanding of different aspects of health conditions experienced by healthy people from all cultures, including children and adolescents (2,3) . On the other hand, the prevalence of depression among adolescents has increased in recent years and has become a public health problem worldwide, with the first episode of depression usually occurring in adolescence (9,13,33) .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have proved that interventions for adolescents can effectively improve the QoL in several dimensions [34]. Peer attachment [52], psycho-emotional status [53], health self-perception [54], social skills [55], and health-related behaviors, such as physical activity [56], are strongly correlated with QoL in adolescents or children. Therefore, measures such as increasing social and family support, reducing negative psychological emotions, improving emotion management skills, learning healthrelated knowledge, and developing healthy habits among adolescents may be effective ways to improve the QoL of adolescents.…”
Section: Discussionmentioning
confidence: 99%